Defensive two-step test in handball players: reliability of a new test for assessing displacement velocity - Ignacio Chirosa-Ríos; Lorenzo Ruiz-Orellana; Daniel Jerez-Mayorga; Luis Javier Chirosa-Ríos; Indya del-Cuerpo; Isidoro Martínez-Martín; Ángela Rodríguez-Perea; Ignacio Pelayo-Tejo; Darío Martinez-Garcia (Federación Extremeña de Balonmano; University of Extremadura, 2023)
The main purposes of this study were to determine the absolute and relative reliability of two-step test (TST) with a functional electromechanical dynamometer (FEMD) in the evaluation of body displacement velocity. Sixteen physically active male handball players volunteers (age 21.4 ± 2.1 years) participated in this study. A repeated-measurement design was used to evaluate body displacement velocity with 15% and 30% of body weight overload (BWO). The mean velocity of the three highest repetitions and the peak velocity for the concentric contractions were taken to calculate the body displacement velocity. Reliability was assessed by t-tests of paired samples with the effect size (ES), the coefficient of variation (CV), standard error of measurement (SEM), and the intraclass correlation coefficient (ICC), with 95% confidence intervals. The absolute reliability provided stable repeatability for the 15% BWO protocol for mean velocity and for peak velocity in both protocols, with CV being below 10% in nearly all instances. The relative reliability of different velocity protocols to evaluate mean and peak velocity was acceptable (ICCs between 0.48 and 0.79). TST has acceptable reliability for the evaluation of the body displacement velocity in handball players using a FEMD.